Intervensi Nurse Social Support pada Keluarga dengan Anak Bronchopneumonia di Ruang ICU RSUD Dr T.C.Hillers Maumere - Maria Alfred; Ode Irman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Bronchopneumonia is one of the world's health problems that occurs in children where the disease is caused by bacteria that enter the bronchi and alveoli. The inflammatory process of bronchopneumonia usually results in an inability to maintain a patent airway. If this condition is not treated immediately it can cause the child to experience severe shortness of breath which can worsen the child's condition so that the child needs to be treated in the Intensive Care Unit. In this case the family has an important role in determining the treatment or method needed by the patient in the intensive care unit. However, families are prone to experiencing anxiety which will slow down the process of decision making and patient care, so it is very important for the role of nurses to overcome family anxiety, one of which is the intervention of Nurse Social Support. The purpose of this study was to identify Nurse Social Support interventions to reduce family anxiety in the ICU. The type/research design used is descriptive method with a case study approach. The subject of this case study is a family that has met the inclusion criteria, namely the client's biological mother with anxiety problems, and is willing to be a respondent. Participant taking technique using purposive sampling. The research instrument for family anxiety used the STAI questionnaire ((State-Trait Anxiety Inventory). The results showed that the Nurse Social Support intervention could reduce the anxiety of the patient's family because the family felt that their interaction with the nurse was an opportunity to share feelings, knowledge and information so they could overcome anxiety.